ASSESSING THE EFFECT OF IRRIGATION WATER QUALITY ON PHYSIOLOGICAL CHARACTERISTICS OF AFRICAN NIGHTSHADE (Solanum Scabrum Mill) - Kamande, Peter; Ndunda, Ezekiel; Kabuyah, Rachel, N. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The use of wastewater for irrigation is widespread across the world. In Nairobi County, many farmers are using untreated sewage to irrigate fodder and crops. However, there is scant literature on the agronomic effect of wastewater irrigation on some of the post popular vegetables grown for the local market. This experimental study was carried out to assess the effect of different qualities of irrigation water on the agronomic parameters of Solanum Scabrum Mill. Different types of water used included wastewater, tap water, water from shallow wells and from borehole. The experiment was carried out under randomized complete block design (RCBD) with four replications. Results show that at day 30, there was a significant difference between the number of mature leaves (p 0.00) and height (p 0.01) between the plant samples grown using tap water as compared to that of shallow well. The results of the study demonstrate that S. Scabrum Mill is affected by the type of quality of the irrigation water used. This is owing to the fact that crops samples grown using shallow wells, recorded the highest mean values of 0.38 (0.02) cm2 , 9.53 (0.37), and 22.81 (0.85) cm as far as the girth area , number of mature leaves, and height are concerned respectively. This is a factor that can be attributed to the high level of nitrogen and phosphates in surficial aquifers due to leaching.